ENZYME-LINKED IMMUNOSORBENT ASSAY BASED ON THE RECOMBINANT VP1 ANTIGEN FOR SEROLOGICAL DIAGNOSIS OF FMD - Mukantayev, K.N.; Shustov, A.B.; Sydyknabi, I.; Inerbay, B.; Bigalyeva, A.; Mukanov , K.K. (Eurasian Journal of Applied Biotechnology, 2014)
Diagnostic tests play an important role in prophylactic and quarantine events against FMD. Therefore, nowadays development of effective methods in diagnostics of diseases is considered as a main problem. Properties of the diagnostic test-systems depend on quality of the used antibodies and antigens. Use of recombinant antigens can improve the diagnostics methods of diseases. The purpose of this study is purification and use of recombinant VP1 antigen for diagnosis of FMD by Enzyme-linked immunosorbent assay. For purification of recombinant antigens there was used metal-affinity chromatography with the column HisTrapTM FF crude (GE Healthcare, Sweden). For the definition of diagnostic properties of antigens by ELISA there were used 186 serum samples of vaccinated animals and 64 serum samples of unvaccinated animals. There have been determined diagnostic properties of VP1 O and VP1 Asia-1 recombinant antigens by means of ELISA. The data obtained showed high effectiveness of the used purification method and suitability of the purified antigens for serological diagnosis of FMD by means of indirect ELISA.